Experimental determination of the kinetics of formation of the benzene‐ethane co‐crystal and implications for Titan. Issue 15 (4th August 2014) - Cable, Morgan L.; Vu, Tuan H.; Hodyss, Robert; Choukroun, Mathieu; Malaska, Michael J.; Beauchamp, Patricia
Abstract Benzene is found on Titan and is a likely constituent of the putative evaporite deposits formed around the hydrocarbon lakes. We have recently demonstrated the formation of a benzene‐ethane co‐crystal under Titan‐like surface conditions. Here we investigate the kinetics of formation of this new structure as a function of temperature. We show that the formation process would reach completion under Titan surface conditions in 18 h and that benzene precipitates from liquid ethane as the co‐crystal. This suggests that benzene‐rich evaporite basins around ethane/methane lakes and seas may not contain pure crystalline benzene, but instead benzene‐ethane co‐crystals. This co‐crystalline form of benzene with ethane represents a new class of materials for Titan's surface, analogous to hydrated minerals on Earth. This new structure may also influence evaporite characteristics such as particle size, dissolution rate, and infrared spectral properties.